The Role of Physical Activity Prescription in Cardiovascular Disease Prevention Amongst South Asian Canadians - Tharmaratnam, Tharmegan; Iskandar, Mina A.; Doherty, Sally; D'Urzo, Katrina A.; Kopalakrishnan, Swana; Tabobondung, Tyler Cameron; Gopee-Ramanan, Prasaanthan; Sivagurunathan, Seyon; Sivananthan, Nirunthan (Frontiers in Cardiovascular Medicine, 2018)
ABSTRACT Unequivocal evidence suggests an increased prevalence of cardiovascular disease (CVD) amongst South Asian Canadians (SACs) compared to other ethnic cohorts, due to a combination of their unique cardiometabolic profile and environmental factors. This unfavourable CVD profile is characterized by an elevated risk of dyslipidemia, high apolipoprotein B/apolipoprotein A1 ratio, hypertension, glucose intolerance, type 2 diabetes mellitus, as well as increased BMI, body fat percentage, abdominal and visceral adiposity. Despite the overwhelming evidence for the effectiveness of physical activity (PA) in circumventing the onset of CVD and in the reduction of CVD risk factors, SACs are among the most physically inactive cohorts in Canada. This relates to a set of common and unique socio-cultural barriers such as gender, beliefs and perceptions about illness, immigration, unfavourable PA environments, and their high prevalence of debilitating chronic diseases. Several strategies to improve PA participation rates in this high-risk population have been suggested, and include the implementation of culturally sensitive PA interventions, as well as clinician training in PA prescription through workshops that emphasize knowledge translation into clinical practise. Therefore, the purpose of this mini-review is to highlight and discuss: (1) the burden of heart disease in SACs (2) the cardiovascular benefits of PA for SACs; (3) factors affecting PA participation among SACs and how they can be addressed; (4) the impact of culturally sensitive PA prescription on CVD prevention; (5) barriers to culturespecific PA prescription by clinicians, and strategies to improve its use and impact.